Lonomia obliqua Walker (Lepidoptera: Saturniidae): hemostasis implications - Maggi,Silviane (2015)
Summary In southern Brazil, since 1989, several cases of accidents produced by unwilling contact with the body of poisonous caterpillars of the moth species Lonomia obliqua Walker, 1855 (Lepidoptera: Saturniidae), were described. L. obliqua caterpillars have gregarious behavior and feed on leaves of host trees during the night, staying grouped in the trunk during the day, which favors the occurrence of accidents with the species. This caterpillar has the body covered with bristles that on contact with the skin of individuals, breaks and release their contents, inoculating the venom into the victim. The basic constitution of the venom is protein and its components produce physiological changes in the victim, which include disturbances in hemostasis. Hemorrhagic syndrome associated with consumption coagulopathy, intravascular hemolysis and acute renal failure are some of the possible clinical manifestations related to poisoning by L. obliqua. Specific laboratory tests for diagnosis of poisoning have not been described previously. The diagnosis of poisoning is made based on the patient's medical history, clinical manifestations, erythrocyte levels, and, primarily, parameters that evaluate blood coagulation. Treatment is performed with the use of supportive care and the administration of specific hyperimmune antivenom. Poisoning can be serious and even fatal.